Analysis of DC-SIGN (CD209) Functional Variants in Patients with Tuberculosis (2006)
Several lines of evidence suggest that host genetic factors controlling the immune response influence infection by Mycobacterium tuberculosis. Recently, DC-SIGN has been shown to be the major M. tuberculosis receptor on dendritic cells (DCs). The aim of this study was to investigate the influence of DC-SIGN functional polymorphisms -336G/A SNP in the promoter region and insertion/deletion in the 'neck' region on the predisposition to tuberculosis. We performed an association study in 110 HIV-negative tuberculosis patients and 299 matched controls. In addition, a total of 155 healthy controls were screened for the tuberculin skin test (TST). DC-SIGN -336 SNP detection was performed by the real-time polymerase chain reaction technology, using the TaqMan 5? allele. The insertion/deletion in the 'neck' region was analyzed by polymerase chain reaction with specific primers. Although an increased frequency of the G allele in tuberculosis patients (23%), as compared with controls (19%), was observed, differences were not statistically significant (OR = 1.31, 95% CI = 0.89-1.94, P = 0.14). On the other hand, DC-SIGN repeat polymorphism in the 'neck' region had a very low frequency in the analyzed population. We conclude that the studied polymorphisms are not relevant risk factors for developing tuberculosis in Northwestern Colombian individuals. © 2006 American Society for Histocompatibility and Immunogenetics.